Functional Narration and Translator Behavior Criticism in the English Translation of Heroes' Names in Outlaws of the Marsh (Journal of humanities and social sciences exploratio, 2026)
This paper focuses on the translation of names of marginal heroes in the English translations of Outlaws of the Marsh , and through a comparative analysis of the full translations by Pearl S. Buck and Sidney Shapiro, delves into the translator behavior characteristics in the context of functional character narration. The study reveals that while Pearl S. Buck's translation pursues fidelity to the original text in naming characters, it also considers the practicality of expression, effectively preserving the authenticity of functional narratives, demonstrating a well-balanced approach between truth-seeking and practicality. Shapiro's translation, on the other hand, while also emphasizing fidelity in naming, exhibits considerations for contextual adaptability in the functional narratives of some characters. Furthermore, both translators frequently employ the "retention" strategy in handling character names, but Shapiro tends to favor "omission" while Pearl S. Buck prefers "transformation" in specific tactics. This research incorporates character naming and functional narrative into the realm of translation criticism, evaluating the translations' performance in conveying the literary essence of the original work from both micro and macro perspectives. It provides a new perspective and theoretical support for the study of English translations of Outlaws of the Marsh.
Keywords: Outlaws of the Marsh; English translations; Functional character narrative